Europec/Eage Conference and Exhibition 2008
DOI: 10.2118/113597-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Flow Skin Factor Formulation for Hydraulically Fractured Wells in Gas Condensate Reservoirs

Abstract: Fracturing is one of the most common well stimulation techniques especially for tight gas-condensate reservoirs. Gas condensate flow around hydraulically fractured wells (HFWs) is different from conventional gas oil systems. This is mainly due to phase change, condensate drop out and coupling (i.e., the increase of relative permeability as velocity increases and/or interfacial tension decreases) and inertial (i.e., the reduction of relative permeability as velocity increases) effects. Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several studies have been done on turbulence effects in hydraulically fractured gas wells (Wang and Economides, 2004;Gil et al, 2001;Lolon et al, 2004;Kakar et al, 2004;Miskimins et al, 2005;Ouyang, 2007;Huang and Ayoub, 2007;Friedel et al, 2007;Nashawi, 2007) and gas condensate wells Indriati et al, 2002;Ravari and Ibrahim, 2005;Ravari et al, 2007;Mahdiyar et al, 2008). Studies (Gil et al, 2001;Ubani and Evans, 1982) showed that significant turbulence flow can exist in a fracture at any time in the life of a vertically fractured gas well.…”
Section: Turbulence In Hydraulically Fractured Vertical Gas Wellmentioning
confidence: 99%
“…Several studies have been done on turbulence effects in hydraulically fractured gas wells (Wang and Economides, 2004;Gil et al, 2001;Lolon et al, 2004;Kakar et al, 2004;Miskimins et al, 2005;Ouyang, 2007;Huang and Ayoub, 2007;Friedel et al, 2007;Nashawi, 2007) and gas condensate wells Indriati et al, 2002;Ravari and Ibrahim, 2005;Ravari et al, 2007;Mahdiyar et al, 2008). Studies (Gil et al, 2001;Ubani and Evans, 1982) showed that significant turbulence flow can exist in a fracture at any time in the life of a vertically fractured gas well.…”
Section: Turbulence In Hydraulically Fractured Vertical Gas Wellmentioning
confidence: 99%